PECULIARITIES OF HYBRID TEACHING FORMAT IMPLEMENTATION IN ENGLISH CLASSES - Zhantleyeva, M.Т.; Turganbayev, А.А. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
This report is devoted to a discussion of the features of the hybrid training format, since this training format is gaining relevance and its implementation requires certain conditions.Thanks to the broad presentation and utilize of computers, instruction has gotten to be by and large open. Numerous individuals utilize different applications to memorize dialects, get unused data, plan for exams. The notoriety and plausibility of creating online courses permitted college instructors to combine distinctive groups, as a result of which understudies ceased to be ―passive‖ audience members and became dynamic members within the handle. The article talks about advanced instructive innovations (applications, stages and other programs) that can be connected as portion of a half breed shape of instruction.
Keywords: hybrid learning; online course; information and communication technologies; planning and organization of the educational process; online platform; online application